The Hart-Fuller debate in the twenty-first century - Hart-Fuller Colloquium (2008 : Canberra, A.C.T.); Cane, Peter, 1950- (Oxford : Hart Pub., 2010)
This book presents the papers and comments on those papers delivered at a colloquium held at the Australian National University in December 2008 to celebrate 50 years since the publication in the Harvard Law Review of the famous and wide-ranging debate between H.L.A. Hart and Lon L. Fuller
Includes bibliographical references and index
Keywords: Hart, H. L. A. -- 1907-1992 -- Congresses; Fuller, Lon L. -- 1902-1978 -- Congresses; Law -- Philosophy -- Congresses